2021
DOI: 10.1001/jamanetworkopen.2021.6842
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Corrected QT Interval Changes Among Patients Treated for COVID-19 Infection During the Early Phase of the Pandemic

Abstract: IMPORTANCECritical illness, a marked inflammatory response, and viruses such as SARS-CoV-2 may prolong corrected QT interval (QTc). OBJECTIVE To evaluate baseline QTc interval on 12-lead electrocardiograms (ECGs) and ensuing changes among patients with and without COVID-19. DESIGN, SETTING, AND PARTICIPANTS This cohort study included 3050 patients aged 18 years and older who underwent SARS-CoV-2 testing and had ECGs at Columbia University Irving Medical Center from March 1 through May 1, 2020. Patients were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 39 publications
3
45
2
1
Order By: Relevance
“…COVID-19 patients are at risk of prolonged QT intervals, even in the absence of antiviral drugs known to increase QT interval. 3 , 4 In our survey, only one-third of the ICUs routinely monitored QT interval. Inadequate ECG monitoring in the prone position may lead to undetected QT-interval prolongation, which increases risk of ventricular arrhythmias.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…COVID-19 patients are at risk of prolonged QT intervals, even in the absence of antiviral drugs known to increase QT interval. 3 , 4 In our survey, only one-third of the ICUs routinely monitored QT interval. Inadequate ECG monitoring in the prone position may lead to undetected QT-interval prolongation, which increases risk of ventricular arrhythmias.…”
Section: Discussionmentioning
confidence: 97%
“…This is particularly true for the QT interval, whose prolongation, frequently observed in COVID-19 patients, exposes them to life-threatening ventricular arrhythmias. 3 , 4 However, it can be difficult to properly monitor the ECG of patients treated with prone positioning, a procedure widely adopted to improve outcomes and indicated for at least 16 h per day in case of moderate-to-severe ARDS. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…In their cohort, patients were older (74 vs 61 years) and had higher over-all mortality (46% vs 28%) compared to our study, which may account for some of the differences between our study and theirs. Previous studies reported longer QT interval in patients with COVID-19 compared to patients without COVID-19 [ 40 ] and QT prolongation after falling ill with COVID-19 compared to before [ 41 ]. Previously reported QT intervals ranges from a mean of 443–450 ms [ 40 43 ], which is somewhat longer than the mean of 440 ms reported in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported longer QT interval in patients with COVID-19 compared to patients without COVID-19 [ 40 ] and QT prolongation after falling ill with COVID-19 compared to before [ 41 ]. Previously reported QT intervals ranges from a mean of 443–450 ms [ 40 43 ], which is somewhat longer than the mean of 440 ms reported in this study. This difference may at least in part be explained by that the present study includes younger patients and fewer patients with previous heart disease, both of which are risk factors for QT prolongation [ 40 , 41 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that QT prolongation can develop independently in recent research. Rubin et al 4) found that COVID-19 infection had a prolonged corrected QT interval (QTc) in hospitalized patients than those without COVID-19 infection. It is intriguing that 25.0% of patients with COVID-19 who had not received hydroxychloroquine nor azithromycin still had a QTc interval of 500 ms or greater, compared with 10.8% of their COVID-negative peers.…”
mentioning
confidence: 99%